Expanding the ichnological record of the Late Paleozoic Ice Age: Evidence from the Santa Fé Group, São Francisco Basin (Brazil) - de Barros, Gabriel E.B.; do Carmo, Dermeval Aparecido; de Andrade, Luiz Saturnino; Assine, Mario Luis [UNESP]; Sedorko, Daniel (Elsevier, 2025)
The Late Paleozoic Ice Age (LPIA) left a significant sedimentary record across Pangea. In Brazil, although the Paraná Basin has provided extensive records of glacial dynamics, the contemporaneous deposits of the Santa Fé Group in the São Francisco Basin (Minas Gerais state) remain comparatively underexplored. These strata preserve a variety of glacially influenced facies, including diamictites, rhythmites, glaciofluvial sandstones, and outsized clasts, but their ichnological content has not been systematically assessed. Here it is presented a detailed analysis of trace fossil assemblages from these deposits, documenting low-diversity ichnoassemblages (Cruziana problematica, Cruziana diplopoda, Diplichnites gouldi, Diplopodichnus biformis, Rusophycus carbonarius, and Helminthoidichnites tenuis) preserved in association with glaciogenic facies. The ichnofossils assist in the recognition of glacial processes on benthic colonization, substrate conditions, and ecosystem recovery during deglaciation phases. By expanding ichnological data beyond the Paraná Basin, these results highlight the potential of the Santa Fé Group to refine paleoecological and paleogeographic reconstructions of Gondwanan icehouse systems, and to better characterize the environmental signatures of the LPIA in Brazil.